Serum Spermidine in Relation to Risk of Stroke: A Multilevel Study - Zheng, Liqiang; Xie, Yanxia; Sun, Zhaoqing; Zhang, Rui; Ma, Yanan; Xu, Jiahui; Zheng, Jia; Xu, Qianyi; Li, Zhao; Guo, Xiaofan; Sun, Guozhe; Xing, Fuguo; et al. (Frontiers in Nutrition, 2022)
The relationship between serum spermidine levels and future cardiovascular disease risk has not yet been well elucidated in the general population based on community studies. Using a nested case-control study, we estimated the association between serum spermidine level and future stroke. New stroke cases had higher baseline levels of spermidine than controls (182.8 (141.8–231.5) vs. 152.0 (124.3–193.0), P<0.001). After multivariable adjustment, individuals with spermidine ≥ 205.9 nmol/L (T3) higher risks of stroke (HR 5.02, 95% CI 1.58–16.02) with the lowest quartile (<136.9 nmol/L) as reference. The association between serum spermidine levels and risk of stroke seemed to be consistent and was reproducible in our cross-sectional studies. In addition, comparisons of the areas under receiver operator characteristics curves confirmed that a model including spermidine had better discrimination than without (0.755 vs. 0.715, P=0.04). Here we report a close relationship exists between serum spermidine levels and risk of stroke.